Higher HDL Cholesterol Is Associated with Better Cognitive Function: the Maine-Syracuse Study. (10th November 2014) - Crichton, Georgina E.; Elias, Merrill F.; Davey, Adam; Sullivan, Kevin J.; Robbins, Michael A.
Abstract Few studies have examined associations between different subcategories of cholesterol and cognitive function. We examined relationships between total cholesterol (TC), high-density lipoprotein cholesterol (HDL), low-density lipoprotein cholesterol (LDL), triglyceride levels and cognitive performance in the Maine-Syracuse Longitudinal Study, a community-based study of cardiovascular risk factors. Cross-sectional analyses were undertaken on data from 540 participants, aged 60 to 98 years, free of dementia and stroke. TC, HDL, LDL, and triglyceride levels were obtained. Cognitive function was assessed using a thorough neuropsychological test battery, including domains of cognitive function indexed by multiple cognitive tests. The cognitive outcomes studied were as follows: Visual-Spatial Memory and Organization, Verbal and Working Memory, Scanning and Tracking, Abstract Reasoning, a Global Composite score, and the Mini-Mental State Examination (MMSE). Significant positive associations were observed between HDL-cholesterol and the Global Composite score, Working Memory, and the MMSE after adjustment for demographic and cardiovascular risk factors. Participants with desirable levels of HDL (≥60 mg/dL) had the highest scores on all cognitive outcomes. There were no significant associations observed between TC, LDL, or triglyceride concentrations and cognition. In older individuals, HDL-cholesterol was related to a composite of Working Memory tests and for general measures of cognitive ability when adjusted for cardiovascular variables. We speculate that persons over 60 are survivors and thus less likely to show cognitive deficit in relation to TC, LDL-cholesterol, and triglycerides. Longitudinal studies are needed to examine relations between specific cognitive abilities and the different subcategories of cholesterol. (JINS, 2014, 20, 1–10)